2019
DOI: 10.1016/j.ajog.2018.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to selective serotonin reuptake inhibitors and serotonin norepinephrine reuptake inhibitors and risk for persistent pulmonary hypertension of the newborn: a systematic review, meta-analysis, and network meta-analysis

Abstract: Exposure to SSRIs or SNRIs during pregnancy is associated with an increased risk for PPHN. According to our findings, sertraline ranked as most likely to have the lowest risk for PPHN compared to other SSRIs, suggesting it may have the best safety profile for use in pregnancy in this regard. Further studies are needed to fully establish these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 48 publications
0
50
1
Order By: Relevance
“…SSRIs have been linked to an increased risk of a severe respiratory neonatal con‐dition (persistent pulmonary hypertension of the unborn), but with a small ab‐solute risk of around 3 in 1,000 reported in a recent systematic review 126 .…”
Section: Interventionsmentioning
confidence: 99%
“…SSRIs have been linked to an increased risk of a severe respiratory neonatal con‐dition (persistent pulmonary hypertension of the unborn), but with a small ab‐solute risk of around 3 in 1,000 reported in a recent systematic review 126 .…”
Section: Interventionsmentioning
confidence: 99%
“…The possible effect of non‐SSRIs was assessed in 3 studies. In addition, 1 meta‐analysis by Masarwa et al 14 reported data about effects of the use of SSRIs or SNRIs. None of the meta‐analyses included data on TCAs.…”
Section: Resultsmentioning
confidence: 99%
“…None of the meta‐analyses included data on TCAs. The number of meta‐analyses evaluating individual neonatal outcomes was as follows: autism spectrum disorders, 10 15‐24 ; ADHD, 4 21,23,31,32 ; preterm birth, 4 25‐28 ; persistent pulmonary hypertension, 3 14,33,34 ; low birth weight, 2 25,29 ; and spontaneous abortion, 2 28,30 …”
Section: Resultsmentioning
confidence: 99%
“…In a recent meta-analysis of 11 studies reporting on a total of 156,978 women and their offspring exposed to SRI [73] the risk of PPHN was increased by 82% (OR 1.82, 95% confidence interval 1.31–2.54). Similar figures emerged when restricting the analysis to exposure after 20 weeks of gestation.…”
Section: Neonatal Effectsmentioning
confidence: 99%